Trust no one - Park, Linda Sue (New York : Scholastic, 2012)
"When seven members of their family were kidnapped, thirteen-year-old Dan Cahill and his older sister, Amy, got ready for the fight of their lives. But their enemy, a terrifying group known as the Vespers, remained frustratingly elusive. They stay in the shadows, picking off Cahills one by one. And now the Vespers have landed their most serious blow yet? A blow that strikes at the very heart of the Cahill family. Because Amy and Dan discover that there's a Vesper mole in their innermost circle. Amy and Dan need to smoke out the traitor before the next hostage dies. They have just days to discover who has their back ... and who wants to sink a knife into it."--Cover.
Keywords: Code and cipher stories; Detective and mystery fiction